User Behavior Analysis Using IoT Data - Fotouhi, Azade; Oudi, Marwa; Gueni, Billel; Mabrouk, Mouna Ben (Nordic and Baltic Journal of Information & Communications Technologies, 2021)
While the number of connected objects in the world of Internet of Thing (IoT) is increasing, an efficient and intelligent solution to exploit the huge amount of generated data does not exist. Smart homes powered by IoT devises are able to automate and monitor the every day activities of home owners, and improve the life quality especially for elderly and disabled people. In this paper, we propose a machine learning based model in order to analyze the IoT data and to provide data-driven services. Hence, this will make it possible to extract meaningful information from data and make intelligent decisions in smart environments. Then, the proposed model is evaluated using collected data from IoT devices based on different communication protocols.